Cobalt-immobilized carbon-based nano-catalyst for Csingle bondN cross coupling reaction - Bankar, Shubham R.; Kirdant, Swapnali P.; Jadhav, Vrushali H. (Results in Chemistry, 2022)
<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/cross-coupling-reaction" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about cross coupling reaction from ScienceDirect's AI-generated Topic Pages">cross coupling reaction is very important in synthesis of pharmaceuticals, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/occurrence-in-nature" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about natural products from ScienceDirect's AI-generated Topic Pages">natural products, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/agrochemical" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about agrochemicals from ScienceDirect's AI-generated Topic Pages">agrochemicals, fine chemicals and functional materials. Traditionally, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/palladium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about palladium from ScienceDirect's AI-generated Topic Pages">palladium or copper metals are used for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling reaction. As palladium is expensive, we developed cobalt immobilized carbon-based nano-catalyst Co@CC for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling. In this work, we synthesized non-noble metal-based Co@CC nano-catalyst by <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/carbonization" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about carbonization from ScienceDirect's AI-generated Topic Pages">carbonization of glucose, it’s functionalization followed by immobilization of cobalt on the surface of the catalyst. The catalyst was well characterized. The C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N cross coupling reaction of various aryl <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/halide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about halides from ScienceDirect's AI-generated Topic Pages">halides & amines using Co@CC nano-catalyst was optimized for solvent, reaction temperature & catalyst <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/concentration-condition" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about concentration conditions from ScienceDirect's AI-generated Topic Pages">concentration conditions. The catalyst showed high catalytic activity for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling of various aryl halides & amines to form aryl amines in good to excellent yield up to 91 % in <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/sulfolane" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about sulfolane from ScienceDirect's AI-generated Topic Pages">sulfolane as a solvent at 150 °C. The catalyst showed recyclability up to 5 times. The method developed for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling reaction was noble metal free, ligand free, recyclable, sustainable, economical & environmentally friendly.

Green, practical & scalable approach towards the synthesis of valuable α-keto amides using a metal-free catalyst under solvent-free conditions - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (New Journal of Chemistry, 2023)
alpha-Ketoamides are very important motifs as they are present in many natural products, drugs & biologically important molecules. We synthesized a very simple, cheap, eco-friendly & reusable glucose-based carbonaceous material (GCM), which showed high performance as a catalyst in the oxidative cross-dehydrogenative coupling (CDC) reaction of alpha-ketoaldehydes with amines for the synthesis of alpha-ketoamides. The GCM catalyst was also very efficient for one-pot two-step synthesis of alpha-ketoamides from alpha-ketoalcohols as well. The GCM catalyst was able to catalyze alcohol oxidation in alpha-ketoalcohols followed by CDC reaction with amines to form alpha-ketoalcohols. The reactions were found to proceed smoothly at a low temperature of 50 degrees C using a green & economical metal-free catalyst under base-free, ligand-free & solvent-free reaction conditions to get the corresponding alpha-ketoamides in good to excellent yields. The results demonstrated that the GCM catalyst showed acidic as well as superior oxidising catalytic activity due to the presence of a carboxylic acid (-COOH) and hydroxyl (-OH)-enriched carbonaceous framework, which enabled the synthesis of important alpha-ketoamide motifs. The applicability of the catalyst was also evaluated for the synthesis of an anti-HIV agent drug molecule. Greener, cheaper & eco-friendly GCM catalyst as well as catalytic process for synthesis of alpha-Keto Amides.

Alternative synthetic route for the pharmacophore of anticancer agent: triazolopyridazine derivative - Karche, Ranjit S.; Bankar, Shubham R.; Jadhav, Vrushali H. (Tetrahedron Letters, 2024)
ATAD2 has received attention as one of the potential oncogene with tumor-promoting aspects in many malignancies. ATAD2 is a highly conserved bromodomain family protein that exerts its biological functions by mainly AAA ATPase and bromodomain. Several small molecule inhibitors have been described in the literature. AZ13824374 (1) recently reported by Holt and co-workers showed promising in vitro (bio-chemical, cellular) and antiproliferative activity in range of breast cancer models. In this work, we described scalable synthetic route for triazolopyridazine derivative (2), a key intermediate of AZ13824374 (1) without using CO in the process. Triazolopyridazine helps to attain the bioactive conformation for AZ13824374 (1) through its crucial interaction with Tyr 1021 of ATAD2. Additionally, triazolopyridazine is extensively used as an intermediate for anticancer agents. This encouraged us to develop cost-effective and scalable process for it.
Keywords: Alternative process; Anticancer; Triazolopyridazine

Direct oxidation of alcohols to carboxylic acids using simple and economical Pd@Glu-HTC catalyst: practical and scalable approach towards biomass based value added chemicals - Kirdant, Swapnali P.; Bankar, Shubham R.; Jadhav, Vrushali H. (Biomass & Bioenergy, 2024)
Sustainable catalytic transformation of bio-based alcohols to high value-added fine chemicals is an important topic of research. This work described preparation of simple and economical Pd@Glu-HTC catalyst from biomass derived low cost D-glucose. Hydrothermal carbonization of glucose was carried out in first step to synthesize GluHTC support in a simpler, greener, economical and efficient manner followed by incorporation of palladium metal on surface of the catalyst in second step. The catalyst was characterized using techniques such as Fourier Transform Infrared Spectroscopy (FT-IR), Solid-state Cross-Polarization Magic Angle Spinning Carbon-13 (13C CPMAS), Energy-dispersive X-ray spectroscopy (EDAX), Powder X-ray diffraction (P-XRD), X-ray photoelectron spectroscopy (XPS), Thermogravimetric/Differential Thermal Analyzer (TG-DTA), Field emission scanning electron microscopy (FE-SEM) and High-resolution transmission electron microscopy (HR-TEM). The catalyst was evaluated for direct oxidation of alcohols to yield carboxylic acids and exhibited very good catalytic activity for wider substrate scope. Oxidation of alcohols was carried out using milder base, molecular oxygen and water as a solvent to achieve 92-99 % excellent yields. The practical utility of current strategy was also studied for gram scale synthesis of bio-based value added industrially important chemicals such as furoic acid (flavouring agent and preservative in industry), 2, 5-furan-dicarboxylic acid (monomer to 100 % fossil-free, recyclable polymer polyethylene furanoate (PEF), tetrahydro-2-furoic acid (production of many drugs) and vanillin (important product of flavor and fragrance industry). Pd@Glu-HTC catalyst was found to be reusable for four recycles and the catalytic performance was retained without any loss in its activity after four cycles.
Keywords: Bio-based chemicals; Carbonaceous catalyst; Carboxylic acid; Oxidation

Selective oxidation of biomass derived 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) over spent dry cell battery cathode material (BCM-2) - Ghadge, Sambhaji S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ACS Applied Engineering Materials, 2024)
Widespread use of batteries across the globe generates a huge amount of waste. This work is the first to report spent dry cell (Zn-Carbon) battery cathode material (BCM-2) as a heterogeneous catalyst for selective synthesis of fine chemical 2,5-diformylfuran (DFF). Cathode material was easily separated from spent batteries, and acid leached followed by calcination to obtain black powder that was denoted as BCM-2. The catalyst was characterized using various techniques such as P-XRD, EDAX, SEM, HR-TEM, TGA, XPS, and BET analysis. Superior catalytic activity was shown by the catalyst for selective formation of DFF using molecular O2 as a sole oxidant. The catalyst was found to give excellent HMF conversion of 97% with 98% high selectivity of DFF. The BCM-2 catalyst was easily recycled and reused without any significant loss in its catalytic activity. This is one of the best examples for a sustainable, cost-effective, and highly efficient catalytic system for the synthesis of the value-added chemical DFF.

Modification of some steps in the synthesis of Ivacaftor by mechano-chemical approach - Bankar, Shubham R.; Jadhav, Vrushali H. (Sustainable Chemistry for Climate Action, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Recently implementation of the mechano-chemistry approach for carrying out some of the steps in the synthesis of API’s, is considered an attractive and environment friendly approach as it permits solvent-free reactions or the use of activators for the reaction, making the process efficient and economical. In this study, we focused on the modification of some steps in the drug Ivacaftor, which is one of the most expensive drugs in the market. For the first time, a mechano-chemical approach was employed to replace some steps in the synthesis of Ivacaftor. One of the fragment 5-amino-2,4-di‑tert‑butyl‑phenol (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">5<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) required in the synthesis of Ivacaftor was prepared in two steps from commercially available 2, 4-bis(1,1-dimethylethyl)-5-nitrophenyl methyl carbonate (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">6<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) by mechano-chemistry approach in good yields. In the last step, fragment 5-amino-2,4-di‑tert‑butyl‑phenol (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">5<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) was coupled with 4-quinolone-3-carboxylic acid <span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">(4)<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> using mechano-chemistry to obtain Ivacaftor (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">1<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) in good yields. The advantage of this methodology was it avoided the use of solvent in all three steps of ivacaftor synthesis, making the process efficient and economical.

Liquid-assisted grinding mechanochemical approach for direct amidation of pyridone-carboxylic acid to synthesize an intermediate used in anti-viral API's bictegravir and cabotegravir - Karche, Ranjit S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ChemistrySelect, 2026)
Mechanochemistry is viewed as an appealing alternative for the synthesis of various compounds, since it is regarded as an eco-friendly and economical method that can be performed under solvent-free reaction conditions. In this work, neat grinding and liquid-assisted grinding (LAG) methods for direct amidation of pyridone-carboxylic acid and 2,4,6-trifluorobenzylamine/2,4-difluorobenzylamine were studied using EDC.HCl as a coupling reagent to synthesize important intermediates used in the synthesis of anti-HIV drug molecules bictegravir, cabotegravir, and dolutegravir. The products were easy to separate as they easily precipitated out from water, and the purity of the products obtained was similar to 97% for the intermediates, thus avoiding the need for their purification. This process eliminated the use of organic solvents for the reaction as well as for the work-up and product purification. The reaction was scaled up on a 15-g scale, giving good yields of the intermediates. The process was found to be practical, scalable, and reproducible on a gram scale.
Keywords: amidation; bictegravir; cabotegravir; mechanochemistry

One-pot tandem oxidative-wittig olefination of primary alcohols using spent battery material as a heterogeneous catalyst in green solvent GVL - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Catalysis Letters, 2026)
Extensive global utilization of dry cell batteries resulted in generation of huge amount of battery waste. Up-cycling of spent battery waste material as a heterogeneous catalyst is an emerging area of research. Cathode material from spent dry cell battery (Zinc-carbon) was isolated, acid leached and calcined to obtain BCM-2 which was used as a heterogeneous catalyst for one-pot tandem oxidative-Wittig olefination in & upsih;-valerolactone (GVL) a bio-based green solvent at a temperature of 50 degrees C. Reaction was found to proceed smoothly using an economical catalyst and environment friendly conditions to get olefins in good yield up-to 74%. The catalyst was found to be reusable for four cycles. The reaction was carried out two-steps in one pot using spent battery material as a catalyst in GVL as a solvent under mild reaction conditions and the applicability of catalyst was shown in 13 examples. The catalyst's effectiveness was also assessed in synthesis of (E)-3, 4 `, 5-trimethoxy-trans-stilbene, an intermediate for biologically active Resveratol.
Keywords: One-pot; Oxidation; Spent battery; Wittig olefination